2005
DOI: 10.1038/nbt1073
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus serotype 8 efficiently delivers genes to muscle and heart

Abstract: Systemic gene delivery into muscle has been a major challenge for muscular dystrophy gene therapy, with capillary blood vessels posing the principle barrier and limiting vector dissemination. Previous efforts to deliver genes into multiple muscles have relied on isolated vessel perfusion or pharmacological interventions to enforce broad vector distribution. We compared the efficiency of multiple adeno-associated virus (AAV) vectors after a single injection via intraperitoneal or intravenous routes without addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
408
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(426 citation statements)
references
References 47 publications
16
408
2
Order By: Relevance
“…Interestingly, PLB downregulation to 20% was sufficient to mediate maximal increase in the Ca 2+ affinity of SERCA2a; further reduction had no additional effect. There was a steady loss of responsiveness to PKAdependent Ca 2+ uptake stimulation by PLB-shRNA, and complete loss of responsiveness was observed on days [22][23][24][25] if the RNAi effect is needed only temporarily in an acute and potentially reversible condition (e.g. HF due to viral or autoimmune myocarditis).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, PLB downregulation to 20% was sufficient to mediate maximal increase in the Ca 2+ affinity of SERCA2a; further reduction had no additional effect. There was a steady loss of responsiveness to PKAdependent Ca 2+ uptake stimulation by PLB-shRNA, and complete loss of responsiveness was observed on days [22][23][24][25] if the RNAi effect is needed only temporarily in an acute and potentially reversible condition (e.g. HF due to viral or autoimmune myocarditis).…”
Section: Discussionmentioning
confidence: 99%
“…Within the framework of our proof-of-concept study that introduces a novel PL-shRNA tool, we have not performed in vivo work, as the efficacy of PLB ablation for HF therapy in animal models has already been demonstrated. 5,[18][19][20][21] In future cardiac gene therapy studies, we will use pseudotyped AAV8 and AAV9 vectors, as two recent studies 26,27 have demonstrated important advantages of these pseudotypes over lentiviruses, adenoviruses and previously used AAV vectors. One remaining challenge is the modification of the cassette in such a way as to allow exogenously regulatable shRNA expression and adjustment of the degree of PLB modulation to changing physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Essentially the same phenomenon is seen following vector delivery to neonatal mice, where high rates of hepatocellular proliferation result in almost complete clearance of episomal vector genomes within two doublings of liver mass occurring within the first 1-2 weeks of life. 17,18 A stable basal level of transgene expression, probably reflecting vector integration, persists thereafter in up to 8% of hepatocytes depending on the vector dose used. In human infants the first doubling of liver mass takes considerably longer, 8-9 months, and the second doubling a further 3 years.…”
Section: Impact Of Proliferation In Target Cell Populationsmentioning
confidence: 99%
“…More than 100 genotypes of AAV have been identified that fall into nine antigenically different genetic clades (Gao et al, 2004). More than 100 genotypes of AAV have been identified that fall into nine different antigenic genetic clades (Gao et al, 2004;Gao et al, 2005) but only AAV1-10 have been engineered into vectors (Davidson et al, 2000;Gao et al, 2005;Gao et al, 2002;Huszthy et al, 2005;Wang et al, 2005). Production of rAAV has been improved recently and extremely high titer pure virus is commonly obtained (Zolotukhin et al, 2002).…”
Section: Adeno-associated Virusmentioning
confidence: 99%